EKSTRAKURIKULER MUSIK MENGGUNAKAN METODE DRILL DI SMA NEGERI 5 BUKITTINGGI - Aditya Putra Yunaldo; Syeilendra (Universitas Negeri Padang, 2026)
This study aims to describe the implementation of music extracurricular activities using the drill method at SMA Negeri 5 Bukittinggi. This type of research is qualitative research with a descriptive approach. The research instrument was the researcher themselves, assisted by notes from extracurricular activities and recordings of music practice. Data was collected through observation, interviews, literature study, and documentation. The steps in analyzing the data were data reduction, data presentation, and drawing conclusions. The results of the study indicate that the drill method in the mixed ensemble music extracurricular activities at SMA Negeri 5 Bukittinggi is effective in improving technical skills, fostering collaboration, and shaping students' character. This program serves as a strategic platform for developing musical talent and preserving local culture, although it still requires optimization of practice time and additional facilities for further development. The drill method has proven to improve students' technical skills in ensemble music performance. Students need 3-4 repetitions to master a pattern of play thoroughly. Through systematic repetitive practice, students develop muscle memory that allows them to execute playing techniques automatically. The variation in practice patterns applied by the instructor prevents boredom and increases student enthusiasm, making the drill method effective for mastering ensemble music skills. Music extracurricular activities also develop students' collaborative skills, which are essential in ensemble learning. This activity requires students to work together, listen to each other, and adjust the game with other group members. The peer tutoring system reinforces the value of cooperation by sharing knowledge between senior and junior students, while also building students' self-confidence and commitment to preserving local culture.